2010
DOI: 10.1206/3701.2
|View full text |Cite
|
Sign up to set email alerts
|

Leech Collections from Washington State, with the Description of Two New Species ofPlacobdella(Annelida: Glossiphoniidae)

Abstract: An assessment of the hirudinifauna of Washington State is presented. in total, 11 distinct leech species were found representing two new records for the state and two new species of the genus Placobdella, both described herein. Placobdella kwetlumye, n. sp., and Placobdella sophieae, n. sp., both collected in Squires Lake, Whatcom County, are morphologically similar to P. burresonae and P. pediculata respectively, but exhibit morphological features that readily separate them from congeners. in addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, it is also morphologically similar to Placobdella sophieae ( Oceguera-Figueroa et al 2010 ) and Placobdella picta (Verrill, 1872). Placobdella sophieae also has 6 rows of dorsal papillae, but it is near transparent green and does not possess a nuchal band or unpigmented to sparsely pigmented patches ( Oceguera-Figueroa et al 2010 ) as found in Placobdella appalachiensis . Additionally, Placobdella sophieae is only known from its type locality of northern Washington ( Oceguera-Figueroa et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is also morphologically similar to Placobdella sophieae ( Oceguera-Figueroa et al 2010 ) and Placobdella picta (Verrill, 1872). Placobdella sophieae also has 6 rows of dorsal papillae, but it is near transparent green and does not possess a nuchal band or unpigmented to sparsely pigmented patches ( Oceguera-Figueroa et al 2010 ) as found in Placobdella appalachiensis . Additionally, Placobdella sophieae is only known from its type locality of northern Washington ( Oceguera-Figueroa et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“… Placobdella sophieae also has 6 rows of dorsal papillae, but it is near transparent green and does not possess a nuchal band or unpigmented to sparsely pigmented patches ( Oceguera-Figueroa et al 2010 ) as found in Placobdella appalachiensis . Additionally, Placobdella sophieae is only known from its type locality of northern Washington ( Oceguera-Figueroa et al 2010 ). Placobdella picta has been sporadically reported in the southeastern United States, including Virginia ( Klemm 1982 ; 1985 ), typically in woodland ponds or lakes ( Sawyer 1972 ; Barta and Sawyer 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the analyses performed herein, it was still unknown whether or not Palearctic populations were panmictic, which would be evident if only a single species was present across the continents; the lack of any newly described Palearctic species would certainly suggest that this is the case. Investigations into the genetic diversity of Palearctic members of Placobdella are virtually non-existent (but see Marrone et al, 2016;Vecchioni et al, 2021) and collection efforts have instead largely focused on North American diversity (e.g., Oceguera-Figueroa et al, 2010;Moser et al, 2012aMoser et al, , b, 2014aOceguera-Figueroa & Le ´on-Re `gagnon, 2014;de Carle et al, 2017;Mack et al, 2019). Through largely expanded geographic sampling, our results show that the COI variation between members of ''Placobdella costata'' are in line with the interspecific divergences shown for other, well-differentiated annelid taxa (e.g., Trontelj et al, 1996;Kvist, 2016;de Carle et al, 2017), which indicates that at least five separate species-level taxa are present in the Palearctic.…”
Section: Discussionmentioning
confidence: 99%
“…Like most glossiphoniiform leeches, members of Placobdella display some degree of parental care (they carry their offspring attached to the ventral surface) and are dorsoventrally flattened, often only slightly longer than wide, and can be found attached to the underside of rocks or submerged debris in freshwater settings, as well as attached to their hosts. All species of Placobdella are bloodfeeding and feed mainly on turtles, although some species will also readily feed on other amphibians and aquatic reptiles, as well as fish, birds, and mammals (including humans) (Jones & Woo, 1990;Siddall & Gaffney, 2004;Siddall & Bowerman, 2006;Vamberger & Trontelj, 2007;Moser et al, 2010;Oceguera-Figueroa et al, 2010;Schulz et al, 2011;Cichocka et al, 2021). Their feeding mode and overall high abundance in most freshwater bodies is suggestive of their high impact on ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2013b)d kwetlumye(Oceguera-Figueroa et al, 2010). Except for lightly papillated to non-papillated species such as P. parasitica(Moser et al, 2013a)d nuchalis(Moser et al, 2017), a big diversity in papillation pattern was noted in American papillated Pacobdella species.…”
mentioning
confidence: 98%